Submission by the International Livestock Research Institute (ILRI) on the Sharm El-Sheikh online portal under the four-year Sharm El-Sheikh joint work on implementation of Climate Action on Agriculture And Food Security - International Livestock Research Institute (International Livestock Research Institute, 2023)
This submission is made in accordance with paragraph 18 of decision 3/CP.27 on operationalization of the online portal referred to in paragraph 16 of the above decision for consideration by the Subsidiary Bodies at their fifty-eighth sessions (June 2023).